2016
DOI: 10.1016/j.matpr.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Resistance of Low Alloy Steel after Shot Peening

Abstract: It is well known that shot peening is able to increase the fatigue strength and endurance of metal parts, especially with a steep stress gradient due to a notch. This positive effect is mainly put into relation with the ability of this treatment to induce a compressive residual stress state in the surface layer of material and to cause surface work hardening [1]. In this paper shot peening is applied on the 40NiCrMo7 low alloy steel and subsequently the surface was re-peened with glass beads to decrease the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…Veľký počet dopadov guľôčok a prekrytie jamiek vytvorí pod povrchom rovnomerné tlakové napätie. Pretože väčšina porušení súčiastky únavou alebo koróziou pod napätím sa iniciuje na povrchu, tlakové napätie indukované tryskaním predlžuje čas potrebný na iniciáciu trhliny a tým aj celkovú životnosť súčiastky alebo zariadenia z hľadiska porušenia únavou materiálu [15][16][17][18]. O vplyve technológie tryskania na korózne vlastnosti povrchu ocele Domex 700 patriacej do skupiny HSLA ocelí však nenájdeme žiadnu relevantnú publikáciu, a preto sme sa tejto problematike rozhodli venovať v tejto štúdii.…”
Section: úVodunclassified
“…Veľký počet dopadov guľôčok a prekrytie jamiek vytvorí pod povrchom rovnomerné tlakové napätie. Pretože väčšina porušení súčiastky únavou alebo koróziou pod napätím sa iniciuje na povrchu, tlakové napätie indukované tryskaním predlžuje čas potrebný na iniciáciu trhliny a tým aj celkovú životnosť súčiastky alebo zariadenia z hľadiska porušenia únavou materiálu [15][16][17][18]. O vplyve technológie tryskania na korózne vlastnosti povrchu ocele Domex 700 patriacej do skupiny HSLA ocelí však nenájdeme žiadnu relevantnú publikáciu, a preto sme sa tejto problematike rozhodli venovať v tejto štúdii.…”
Section: úVodunclassified
“…Recent research works also proved that intensity of shot peening process increases the fatigue strength [2]. Fatigue life depends on various factors like relaxation level of the stress layer, surface modification created by peening process and the compressive residual field induced [3]. From experimental investigations, it was observed that enhancement of fatigue life was influenced by arresting crack formation.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, Klocke et al proposed a feasible method for assessing the homogeneity of residual stress distribution on shot peened steel. 17 A review of the past studies has revealed that shot peening effects on fatigue crack initiation and growth were examined by applying this surface treatment technique on the entire surface of the steel samples. They found that the fatigue behaviour of this material improved by surface peening process and the best fatigue performance obtained with the specimens that were shot peened at 20 Almen intensity and 100% saturation.…”
Section: Introductionmentioning
confidence: 99%
“…16 As the last example, Závodská et al studied the effect of shot peening on fatigue strength in a low alloy steel and realised that there is an increasing positive effect on fatigue strength for crack initiation and growth due to shot peening. 17 A review of the past studies has revealed that shot peening effects on fatigue crack initiation and growth were examined by applying this surface treatment technique on the entire surface of the steel samples. However, the influence of partial peening on subsequent fatigue crack growth behaviour is yet to be investigated and compared with full surface treatment.…”
Section: Introductionmentioning
confidence: 99%